Principal’s Performance in Improving the Quality of Educators - Suryadi, Muhamad; Arafat, Yasir; Fahmi, Muhammad (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study examines the role of academic supervision in enhancing teaching quality at SMA Negeri 1 Banyuasin I, addressing observed deficiencies in teacher performance through principal-led supervisory practices. Employing a descriptive qualitative methodology, data was collected through triangulated methods including classroom observations (12 sessions), in-depth interviews (with 1 principal, 8 teachers, and 15 students), and document analysis of 20 lesson plans and supervision records over one academic semester. Findings demonstrate that academic supervision significantly improves teaching quality (evidenced in 78% of observed cases), though current practices overemphasize evaluative inspection rather than developmental guidance. Key outcomes include measurable improvements in pedagogical competence (23% increase in lesson plan quality scores) and classroom management skills. This study introduces a competency-based supervision framework that uniquely integrates: (1) differentiated supervision approaches tailored to teacher experience levels, and (2) a dual focus on technical skills and emotional intelligence in supervisory practice an underexplored dimension in existing literature. The research suggests three actionable strategies for school leaders: implementing cyclical supervision with pre-observation conferences and formative feedback; developing supervisory competency through targeted training in coaching techniques; and establishing professional learning communities to sustain improvement. The study makes dual contributions by: (1) advancing theoretical understanding of effective supervision through its emotional intelligence dimension, and (2) providing an evidence-based model for improving supervisory practices in similar educational contexts. Results indicate this approach could increase teaching effectiveness by up to 35% when fully implemented.